The city as a narrator - Buinov, Alexei; Konyukhova, Nadezhda; Lidin, Konstantin (project baikal, 2025)
The role of signs and symbols in the development of cities is considered within the framework of urban philosophy. It is shown that in many cases the flow of signs degenerates into a flow of empty signs, simulacra, which causes significant damage to the city. The alternative is to organise a flow of emotionally loaded signs. In this case, the city acts as a storyteller (narrator). The article gives the examples of cities successfully developing as narrator cities.
Keywords: architecture; urbanism; signs and symbols; simulacra; Suzdal; Vitebsk